Copper catalyzed five-component domino strategy for the synthesis of nicotinimidamides. Issue 17 (9th April 2021) - Zhao, Yu; Li, Li; Zhou, Zitong; Chen, Man; Yang, Weiguang; Luo, Hui
Abstract : Copper catalyzed five-component domino strategy to synthesize nicotinimidamides via a CuAAC/ring-opening procedure and generate a highly reactive N -sulfonyl acetylketenimine intermediate. Abstract : A library of medicinally and synthetically important nicotinimidamides was synthesized by a copper-catalyzed multicomponent domino reaction of oxime esters, terminal ynones, sulfonyl azides, aryl aldehydes and acetic ammonium. Its synthetic pathway involves the formation of a highly reactive N -sulfonyl acetylketenimine, characterized by high selectivity, combinations of potential nucleophiles and electrophiles, mild reaction conditions and a wide substrate scope, and is a rare five-component example of a CuAAC/ring-opening reaction.